2011
DOI: 10.1002/eat.20791
|View full text |Cite
|
Sign up to set email alerts
|

The refeeding syndrome and glucose load

Abstract: Comprises of a literature review, highlighting this case as the youngest reported case of refeeding syndrome in anorexia nervosa. Discussion focuses on the possible deleterious affects that carbohydrates may have in exacerbating the refeeding syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 36 publications
0
38
0
3
Order By: Relevance
“…There is currently no comprehensive literature on nutrient composition of refeeding regimens in AN, apart from one case study of the refeeding syndrome in which the authors suggested a higher fat versus a carbohydrate regimen may be helpful 39. Therefore, an investigation of the macronutrient composition of refeeding regimens on glucose metabolism and stability of blood glucose values using more rigorous scientific methods is overdue.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no comprehensive literature on nutrient composition of refeeding regimens in AN, apart from one case study of the refeeding syndrome in which the authors suggested a higher fat versus a carbohydrate regimen may be helpful 39. Therefore, an investigation of the macronutrient composition of refeeding regimens on glucose metabolism and stability of blood glucose values using more rigorous scientific methods is overdue.…”
Section: Discussionmentioning
confidence: 99%
“…3 Additionally, there are suggestions that the actual composition of nutrition in refeeding may be more important than the energy content alone. For example, there have been observations that RFS is more likely to occur when carbohydrate is the main source of energy, 10 while feeds that are low in amino acids are less likely to develop hypophosphatemia. 11 Therefore, the recommendations include:…”
Section: Nutritional Supportmentioning
confidence: 99%
“…the amount of energy provided by feed per day) is safest. Although slower rates of feeding intuitively seem safest, many cases of re‐feeding syndrome reported in the literature occur at lower rates than those often commonly used and considered to be conservative in routine clinical practice 35 . A recent retrospective study of re‐feeding syndrome in adolescent AN showed low rates of occurrence at quicker rates of feeding, and where they did occur, they were mild in severity 36 .…”
Section: What Is Underweight In Children and Adolescents?mentioning
confidence: 99%